Pengaruh Usia, Tingkat Pendapatan dan Kepribadian Pada Perilaku Keluhan Konsumen - Chandra, Andri; Jatra, I Made (E-Jurnal Manajemen; Vol 3 No 10 (2014), 2014)
The growing numbers of providers consumers from year to year has increased dramatically. Companies usually considered consumer complaints as an important indicator to measure consumer satisfaction. The goal is to determine the influence of age, income level amd personality of the XL’s consumer complaint behavior. The results of the study was to obtain a positive and significant influence among age, income level and personality of the consumer complaint behavior. XL’s providers add point of service by opening a branch office in small towns to maximize service
Keywords: Age, revenue, personality and consumer complaining behaviour